The Attitude of Undergraduate Students On The Utilization of Flipped Classroom For Learning In South-West, Nigeria - Amos Ochayi Onojah; Adenike Janet Aderogba; Charles Olubode Olumorin; Olubunmi Odewumi; Gboyega Ayodeji Aladesusi (IJER (Indonesian Journal of Educational Research), 2020)
ICT encourages students to improve their literacy and numeracy skills and to recognise their existing abilities. In this critical moment of Technological breakthrough, the reputation of education to mankind cannot be overstressed. The flipped classroom is a pedagogical model in which the typical lecture and homework elements of a course are reversed. The roles of students have a corresponding change from passive participants to positive participation. This study investigated the attitude of undergraduate students towards the use of flipped classroom for learning in South west, Nigeria and also examined the influence of gender and school ownership on their attitude towards the use of flipped classroom. A cross-sectional survey type was adopted in this study. A researcher designed questionnaire was used to collect information. One thousand, eight hundred undergraduate students were randomly selected across twelve universities in South West region of Nigeria. Frequency, mean and percentage was used to analyze the responses to the research questions. Hypothesis 1 was tested using t-test while hypothesis 2 was tested using Analysis of variance (ANOVA) at 0.05 level of significance. The findings established that undergraduate students have positive attitude towards the use of flipped classroom for learning. It was then recommended that stakeholders in education should procure necessary equipment for flipped classroom